(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In this article, according to the "Development Strategy" for 2022-2026, the development of a digital economy in the transformation of the economy in the construction of a new Uzbekistan, the scientific basis for the transformation of the digital economy into a driver industry, as well as practical reforms, opportunities and shortcomings described.